Circulating miR-21-5p and miR-148a-3p as emerging non-invasive biomarkers in thymic epithelial tumors. Issue 1 (2nd January 2016) - Bellissimo, Teresa; Russo, Emanuele; Ganci, Federica; Vico, Carmen; Sacconi, Andrea; Longo, Flavia; Vitolo, Domenico; Anile, Marco; Disio, Daniele; Marino, Mirella; Blandino, Giovanni; Venuta, Federico; et al.
ABSTRACT: Thymic epithelial cells give rise to both thymoma and thymic carcinoma. A crucial advance in thymic epithelial tumors (TET) management may derive from the identification of novel molecular biomarkers able to improve diagnosis, prognosis and treatment planning.In a previous study, we identified microRNAs that were differentially expressed in tumor vs normal thymic tissues. Among the microRNAs resulted up-regulated in TET tissues, we evaluated miR-21-5p, miR-148a-3p, miR-141-3p, miR-34b-5p, miR-34c-5p, miR-455-5p as blood plasma circulating non-invasive biomarkers for TET management.We firstly report that the expression levels of specific onco-miRNAs, that we found upregulated in the blood plasma collected from TET patients at surgery, resulted significantly reduced in follow-up samples.This pilot study suggests that circulating miR-21-5p and miR-148a-3p could represent novel non-invasive biomarkers to evaluate the efficacy of therapy and the prognosis of TET.